Photodynamic therapy for multiple basal cell carcinomas. - Cabrera, Humberto; Castro, Jorge; Grassi, Hilda (Ciencia, 1970)
In this work we describe the use of two chlorin e-6 based photosensitizers (Radachlorin® and Photolon®) to treat multiple basal cell carcinomas. Photodynamic therapy method was applied for two patients with 31 superficial basal cell carcinomas. The presented data show a positive response with an overall rate of 100% complete regression in all treated lesions, and acceptable aesthetic results without serious side-effects or complications during or after treatments. Therefore the photodynamic therapy method with chlorin derivatives appears to be good promising option for the treatment of multiple basal cell carcinomas.